MAKNA SEKSUALITAS DALAM ALQUR’AN MENURUT HUSEIN MUHAMMAD - Muhammad Tobroni (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2017)
The development of interpretation is an inevitability. Interpretation is a process to respond social reality, at once giving the solution for the societal problematic life. For instance, the interpretations of sexuality verses were having the various meaning which is able to be re-interpreted. The interpretation conducted by the classical ulama’ was still leaving some problems, especially on the verses about feminism. This article aims to elaborate the Husein Muhammad thought on the meaning of sexuality in the feminism verses. The analysis tools used is the sociological knowledge of Karl Manheim, in order to be able to understand the context of Husein Muhammad thought as an explanation of the feminism verses. The result of the study showed that Islam is a product of the struggle between religion and culture. So that, Q.S. Alrum 30: 21 must be seen as firstly, as a human way to channeling the libido passion to get sexual satisfaction. Secondly, the human effort is to preserving life on earth, so that marriage is having a function to pro-create and reproduction. Thirdly, as a human way to find out the peace and beautiful place to live in